Conflict Resolution and Conflict Transformation: Some Reflections - Wani, Hilal Ahmad; Suwirta, Andi; Fayeye, Joseph (ATIKAN, 2013)
ABSTRACT: Human beings engage in conflict, aggression, warfare, and violence seemingly equate with the human condition. Equally, humans have sought, as long as there has been conflict, to handle conflict effectively by containing or reducing its negative consequences. This paper is an effort to understand some of the major theoretical perspectives of conflict resolution and conflict transformation. Since both the concepts are very important for giving us kind of understanding that how can we minimize the level and structures of conflicts and to create new avenues of cooperation and compatibility. This study tried to highlight the basic dichotomy between the two concepts. Any conflict can be resolved and transformed if the structure and relationship of the two conflicting parties are fully taken into consideration. Both theories diagnoses causes and sources of conflict and both can be used as methods for resolving and transforming different conflicts. Finally, this paper is the scholarly work for understanding the major differences as well as simillarities between conflict resolution and conflict transformation. KEY WORD: Conflict resolution, conflict transformation, causes of conflict, and conditions for peaceful resolution of conflict.IKHTISAR: Makalah ini berjudul âResolusi Konflik dan Transformasi Konflik: Beberapa Refleksiâ. Manusia terlibat dalam konflik, agresi, perang, dan kekerasan yang nampaknya berjalan seiring dengan kondisi manusia. Pada saat yang sama, manusia juga telah berusaha, sepanjang konflik itu ada, untuk menangani konflik secara efektif dengan mengisi atau mengurangi konsekuensi negatifnya. Makalah ini merupakan upaya untuk memahami beberapa perspektif teoritis utama tentang resolusi konflik dan transformasi konflik. Kedua konsep itu sangat penting untuk memberikan kita semacam pemahaman tentang bagaimana kita bisa meminimalkan tingkat dan struktur konflik serta menciptakan jalan baru bagi kerjasama dan kesesuaian. Penelitian ini mencoba untuk menyoroti dikotomi dasar antara dua konsep tersebut. Setiap konflik dapat diselesaikan dan diubah jika struktur dan hubungan kedua pihak yang berkonflik sepenuhnya dipertimbangkan. Kedua teori mendiagnosa penyebab dan sumber konflik dan keduanya dapat digunakan sebagai metode untuk menyelesaikan dan mengubah konflik yang berbeda. Akhirnya, makalah ini adalah karya ilmiah untuk memahami perbedaan dan kesamaan utama antara resolusi konflik dan transformasi konflik.KATA KUNCI: Resolusi konflik, transformasi konflik, penyebab konflik, dan kondisi untuk penyelesaian konflik secara damai.Â Â Â Â About the Authors: Dr. Hilal Ahmad Wani is a Post Doctoral Fellow at the Centre for Peace & Strategic Studies UOI (University of Ilorin) in Nigeria; Andi Suwitra, M.Hum. is a Senior Lecturer at the Department of History Education UPI (Indonesia University of Education) in Bandung; and Dr. Joseph Fayeye is an Associate Professor at the Centre for Peace & Strategic Studies UOI in Ilorin, Nigeria. They can be reached at: wanihilal@gmail.com, andisuwirta@yahoo.com, and josephfayeye@yahoo.comHow to cite this article? Wani, Hilal Ahmad, Andi Suwitra & Joseph Fayeye. (2013). âConflict Resolution and Conflict Transformation: Some Reflectionsâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.3(1) Juni, pp.35-44. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung and FKIP UNSUR in Cianjur, West Java, ISSN 2088-1290. Chronicle of the article: Accepted (April 8, 2013); Revised (May 17, 2013); and Published (June 15, 2013).